LOS CONTRATOS COMERCIALES: EFECTOS EN LA APLICACIÓN DE LAS NORMAS TRIBUTARIAS - Santa Cruz Miranda, Adolfo (2016)
Due to the vast commercial trade of the current era, in this century modern parameters have been established to determine the ways and goods procurement. The traditional contract of sale has given way to various types of contracts increasingly tailored to specific situations, which has forced countries to have a contractual arrangement that enables adequate development in economic and social matters. In that context, the contract as a legal instrument is continuously modified to the extent that the forms of economic cooperation change between the contracting parties. This work relates to the study of certain contracts, considered as commercial or undertaking contracts, as why it should be examined and / or issued in the light of the rules of the Civil Code, Corporations Act or other specific legal rules in force in the country. These contracts in legal doctrine called “typical” are controlled or regulated by our Peruvian law. Examples of these types of contracts are: contracts binding sale, contracts of sale with reservation of ownership, contracts for the sale of goods on consignment, contracts relating to social contributions, contracts of sale of future goods and contracts, and confirmatory arras and arras of withdrawal.